Accounting scandals and implications for directors: Lessons from Enron - TAN, Pearl Hock-neo (Institutional Knowledge at Singapore Management University, 2022)
We analyze the Enron case to identify the risk factors that potentially led to its collapse and specific issues relating to its aggressive accounting and high-light the lessons for independent directors. In Enron, the interactions between external stimuli, strategies, corporate culture, and risk exposures possibly created an explosive situation that eventually led to its demise. Much of the post-Enron reforms have been directed towards regulating the roles and responsibilities of executive directors and auditors. However, the role of independent directors has received relatively lesser attention. Independent directors should analyze the risks of their companies and understand the pressures that arise from market conditions and firm-specific policies and incentive structures. They also need to close the information gap between executive directors and themselves. A post-Enron era also requires independent directors to change their focus. Traditionally, independent directors have to strike a difficult balance between maximizing returns and minimizing risks. Independent directors may now have to focus on the management of risks, the design and functioning of an effective corporate governance infrastructure, and the moderation of the power bases of dominant executives. Practically, they may also have to reduce the number of independent director appointments to enable them to focus more effectively on a fewer companies.